Adenia angulosa (Passifloraceae), a new species from coastal forests of Kenya and Tanzania - Ngumbau, Veronicah Mutele; Nyange, Mwadime; Dai, Can; Zhong, Zhi-Xiang; Wei, Neng; Malombe, Itambo; Hu, Guang-Wan; Wang, Qing-Feng (Phytotaxa, 2017)
Adenia angulosa, a new species of Passifloraceae from coastal forests of Kenya and Tanzania is described and illustrated with photographs. It is most similar to A. gummifera, but differs by its angled older stem, leaf shape, fewer flowers per inflorescence, connation of filaments, shape of ovary and fruit, as well as size and shape of seed.